Factors Associated with the Causes of Migration among Youth Migrants in Thailand - Phujampa, Kaweesak; Ayuwat, Dusadee (Journal of Arts and Thai Studies, 2025)
Background and Objectives: The transformation of economic and social structures, driven by capitalism, alongside advancements in technology and communication, and the development of infrastructure, have collectively facilitated migration across all age groups. This includes youth migrants, who are either currently enrolled in the formal education system or have recently graduated. Understanding the causes of the migration of the youth migrant group can reflect the opportunities afforded by societal shifts. Therefore, this research aims to investigate the causes of youth migration in Thailand and the factors associated with the causes of youth migration in Thailand. This study focuses on internal migration in Thailand. Methods: Quantitative research with a cross-sectional design was utilized. The unit of analysis was the individual. The sample consisted of 1,917 youth migrants aged 15–24 years at the time of the 2023 survey. The data were derived from the microdata of the Population Migration Survey Project, collected by the National Statistical Office of Thailand between October and December 2023. Descriptive statistics and Chi-square tests were employed to analyze the factors associated with the causes of youth migration in Thailand. The research findings were presented with a narrative accompanied by tables. Results: The results found that the majority of youth migrants were female, single, aged 19–24 years, and had completed upper secondary education. Most originated from the Northeast and South regions, with primary destinations being urban areas in the Northeast, Central, and South regions. Nearly half of this group had resided in their destination areas for less than one year. Regarding the causes of youth migration in Thailand, education was the primary reason for migration, accounting for 54%, followed by family reunification. Specifically, older youth migrants (19–24 years), both male and female, who were single, originated from the Northeast and South, and lived in urban areas, primarily migrated for education. In contrast, younger youth migrants (15–18 years) predominantly migrated to follow their families. Additionally, married or previously married youth migrants with diplomas or higher education primarily migrated for economic reasons. A higher proportion of economic migration was observed among youth migrants who had resided in their destinations for less than one year compared to those who had stayed for more than one year. Application of this study: This study contributes to the development of the body of knowledge on the causes of youth migration. The findings are valuable for policymakers in developing appropriate policies and measures to support youth migrants appropriately, for instance, developing the welfare systems for young migrants or adjusting the economic structure and development to align with the evolving trends of this age group, in order to enable their full potential. Conclusions: This study employed a quantitative research approach using a cross-sectional design, drawing upon the data from the 2023 Migration Survey conducted by the National Statistical Office of Thailand. The sample consisted of 1,917 adolescent migrants aged 15–24 years. The findings revealed that the majority of adolescent migrants were female, single, aged between 19 and 24, and migrated primarily for educational purposes, followed by family-related reasons. The younger adolescents tended to migrate to follow their families, while older and more highly educated individuals migrated mainly for economic reasons. The study indicated that adolescent migration is associated with age group, marital status, educational level, and duration of residence at the destination. These findings can serve as a foundation for formulating policies and measures to better support adolescent migrants in alignment with the current economic and social contexts.